Müllerianosis of cervix. Case report - Reyna-Villasmil, Eduardo (2020)
Müllerianosis is an embryonal disease of the müllerian or paramesonephric ducts, consists in the mixture of two or more types of tissues and results in the formation of adenomyosis, endometriosis, endosalpingiosis, and endocervicosis. It most often affects the urinary bladder in women of childbearing age. Müllerianosis of the cervix is a very rare benign condition, with few reported cases. The exact pathogenesis remains a matter of debate. There are several theories on its etiology; the main two are the implantation and metaplastic theories. Symptoms range from absent to pelvic pain and dysmenorrhea. It generally appears as a cystic tumor with glands of different sizes lined by endometrial, endocervical, or tubal epithelium. This lesion could be confused with other benign, premalignant, or even malignant lesions, and histopathological confirmation is necessary. Because it is a benign disease, no additional treatment is required after surgical resection. A case of müllerianosis of cervix is presented.